Intercultural Sensitivity and Arabic Language Learning: Understanding Students’ Perspectives at MAN 1 Tapin - Fakhrurrozy, Muhammad Imam; Amrullah, M. Kholis; Zahra, Ghinaa Salsabil; Azkiah, Siti (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study investigates the relationship between intercultural sensitivity and Arabic language learning from the perspectives of students at MAN 1 Tapin. Using a qualitative design with semi-structured interviews as the sole data collection method, the research explores how students perceive, experience, and develop intercultural awareness through Arabic learning. Thematic analysis revealed five dominant themes: cultural awareness in Arabic learning, empathy and respect toward cultural difference, communication confidence, openness to cultural diversity, and the role of classroom practices in supporting intercultural learning. The findings indicate that students demonstrate an emerging but positive level of intercultural sensitivity, showing curiosity, tolerance, and growing cultural understanding. However, challenges persist due to limited exposure to authentic Arabic cultural contexts and insufficient integration of intercultural content in the curriculum. The study emphasizes the importance of incorporating intercultural dimensions into Arabic pedagogy to enhance both linguistic and cultural competence. By fostering empathy, openness, and reflective understanding, Arabic language instruction can become a transformative medium for developing global-minded learners.